Value of performance baseline in voluntary carbon trading under uncertainty. (15th February 2018) - Liu, Xiaoyu; Cui, Qingbin
Abstract: Voluntary carbon trading has long been criticized for producing a large number of non-additional offsets. The reason for this production lies primarily in the use of a project-based baseline that misrepresents the business-as-usual (BAU) emissions of individual projects. Performance baseline however, as an alternative baseline approach, does not rely on evaluating individual BAU emissions. Instead, it uses a pre-defined emission threshold for a class of project activities. This paper compares the effects of the two baseline approaches on sectoral emission mitigation and compliance costs by modeling dynamic emission abatement behaviors. In the context of the U.S. commercial building sector, the modeling results indicate that while both baseline approaches are capable of reducing sectoral emissions, the use of performance baseline is especially advantageous under private cost information and uncertain market environments. The performance baseline should be stratified by region to ensure the equity in offset allocation in sectors that are highly diversified in emission magnitudes. Highlights: Two types of baseline are compared regarding the effect on emission abatement. Dynamic emission reduction for buildings are modeled under two baseline scenarios. Performance baselines are often cost-effective to achieve emission reduction. Performance baselines should be stratified by region.